2D and 3D Digital Image Correlation in Civil Engineering – Measurements in a Masonry Wall. (2015) - Ramos, Tiago; Furtado, André; Eslami, Shayan; Alves, Sofia; Rodrigues, Hugo; Arêde, António; Tavares, Paulo J.; Moreira, P.M.G.P.
Abstract: Reinforced concrete structures play an important role in modern buildings, and common architectural designs often include RC frames strengthened with infill masonry panels. Due to their brittle nature, these components' failure and collapse have been subject of studies which can lead to proper structural diagnose and design in order to decrease their risk to human lives during seismic activities. Digital image correlation was used in two of these studies, in order to validate its ability for large specimens monitoring and future structural health monitoring applications. It enabled spatial reconstruction of the wall movement, characterization of its rigid body motion and measurement of both displacements and strain fields in in-plane and out-of-plane load applications. Data post-processing allowed the identification of common in-plane damages in the wall such as corner crushing and separation between infill and resistant structure.